Detection Pork Oil and Palm Oil Using Light Intensity Parameters - Amaliya, Virginia Fahriza; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2020)
To distinguish between pork oil and palm oil, we can use the characteristics of light absorbtion from the material. So, in this research we set a detection method using light intensity as the parameters. Equipment that we used are LDR sensors and red LED as the light source. Pork oil and palm oil were varied into two types of treatment, namely oil with no filtering and a single filtering. In this experiment we got that pork oil has higher light intensity than palm oil. It means that palm oil more absorb the light than pork oil. So, we conclude that light intensity can distinguish the type of oil. Further study is needed so we can develope more accurate and simple detection tool to determine the type of oil especially pork oil in order to give information about halal food for muslim.